2016
DOI: 10.1159/000450882
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition in Very Preterm Infants: Role of Neonatal Characteristics and Nutrition in Achieving Growth Similar to Term Infants

Abstract: Background: The identification of factors involved in the postnatal growth of preterm infants will help achieve growth similar to that of term infants. Objectives: As per protocol: to compare body composition in very preterm infants at term-corrected age (TCA) with that in term infants, and to explore relationships between neonatal characteristics and body composition in preterm infants. Methods: Anthropometry, nutritional characteristics, and neonatal outcomes were prospectively collected in 26 preterm (<29 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 26 publications
3
21
1
1
Order By: Relevance
“…-1 z-score), with the remaining infants 11.4 and 18.3 g/kg/day reported for very preterm infants in previous studies. 14,19,47 Similarly to our results, a study in preterm infants receiving early low nutrient intakes showed mean velocities varying between 9.4 and 11.3 g/kg/day. 22 Despite of the low in-hospital weight gain velocity, the body weight (0.139, p ¼ 0.205), length (0.247, p ¼ 0.681), head circumference (-0.37 cm, p ¼ 0.358), and FM% (0.469, p ¼ 0.589) of our infants at term equivalent age were similar to the values reported by Roggero et al 47 In our sample, no significant differences were found in any body composition measurement, either between sexes or between the extremely preterm and very preterm infants.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…-1 z-score), with the remaining infants 11.4 and 18.3 g/kg/day reported for very preterm infants in previous studies. 14,19,47 Similarly to our results, a study in preterm infants receiving early low nutrient intakes showed mean velocities varying between 9.4 and 11.3 g/kg/day. 22 Despite of the low in-hospital weight gain velocity, the body weight (0.139, p ¼ 0.205), length (0.247, p ¼ 0.681), head circumference (-0.37 cm, p ¼ 0.358), and FM% (0.469, p ¼ 0.589) of our infants at term equivalent age were similar to the values reported by Roggero et al 47 In our sample, no significant differences were found in any body composition measurement, either between sexes or between the extremely preterm and very preterm infants.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, other studies based on estimated or measured nutrient intakes found that, in preterm infants at term equivalent age, specific body compositions were associated with different nutritional strategies. In these studies, higher protein 15,19 and PER 18 intakes were associated with an increase in lean mass 18,19 and decrease in adiposity, 14 while higher fat and energy intakes were associated with increased fatness. 15 We used a nested case-control analysis to explore the associations between cumulative in-hospital nutrient intakes and extremes of adiposity 46 at term equivalent age.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The development of the measurement technique with the DXA method has led not only to its increased accuracy, but also its use in extreme age groups, such as infants [10] or even preterm infants [11]. Lack of age restrictions is an important advantage of DXA as compared to other two-component methods.…”
Section: Densitometry With Double-ray X-ray Techniquementioning
confidence: 99%
“…A protein intake with a goal of 4g/kg/day in VPT infants during their first week of life had a positive association with FFM before hospital discharge (Ramel, Gray et al 2016). Protein intake with a mean of 2.9 g/kg/day during the first week of life in VPT infants had also a positive association with FFM at a mean of 39.5 weeks (Tremblay, Boudreau et al 2017). In a randomized control trial, a significant improvement in lean body weight of some 300g was seen in VPT infants at term, after the introduction of a protein intake of 3.6 g/kg/d compared to 2.7 g/kg/d (Uthaya, Liu et al, 2016).…”
Section: Proteinmentioning
confidence: 93%